Correlates of physical activity habits in adolescents: A systematic review - Shao, Tianyi; Zhou, Xiaogang (Frontiers in Physiology, 2023)
Physical activity habits are crucial for the physical and mental well-being of adolescents (individuals aged 10–19 years). However, few studies over the last two decades have systematically aggregated the influential factors of physical activity habits of adolescents. Five online databases (EBSCO host (Eric), Psychology and Behavioral Sciences Collection, PubMed, Scopus, Web of Science) were searched for relevant studies published before August 14, 2022. Our systematic review indicated the following: 1) boys performed more physical activity habits than girls, while girls preferred to engage in moderate-to-vigorous physical activity; 2) physical activity in adolescents decreased with age; 3) African American adolescents performed significantly more habitual physical activity than white adolescents; 4) adolescents with higher literacy had better physical activity habits; 5) support from parents, teachers, friends, and others helped adolescents develop physical activity habits; 6) adolescents who spent less time participating in habitual physical activity had a higher body mass index; 7) adolescents who reported higher levels of self-efficacy and satisfaction with school sports tended to have stronger physical activity habits; 8) sedentary behavior, smoking, drinking, prolonged screen time, negative emotions, and excessive use of media technology were correlated with reduced habitual physical activity in adolescents. These findings could help develop interventions to motivate adolescents and promote physical activity habits among them.